Subsurface imaging reveals a confined aquifer beneath an ice‐sealed Antarctic lake. Issue 1 (12th January 2015) - Dugan, H. A.; Doran, P. T.; Tulaczyk, S.; Mikucki, J. A.; Arcone, S. A.; Auken, E.; Schamper, C.; Virginia, R. A.
Abstract Liquid water oases are rare under extreme cold desert conditions found in the Antarctic McMurdo Dry Valleys. Here we report geophysical results that indicate that Lake Vida, one of the largest lakes in the region, is nearly frozen and underlain by widespread cryoconcentrated brine. A ground penetrating radar survey profiled 20 m into lake ice and facilitated bathymetric mapping of the upper lake basin. An airborne transient electromagnetic survey revealed a low‐resistivity zone 30–100 m beneath the lake surface. Based on previous knowledge of brine chemistry and local geology, we interpret this zone to be a confined aquifer situated in sediments with a porosity of 23–42%. Discovery of this aquifer suggests that subsurface liquid water may be more pervasive in regions of continuous permafrost than previously thought and may represent an extensive habitat for microbial populations.